Taxonomic and functional β-diversity of Collembola across elevational and seasonal gradients on a temperate mountain - Zhijing Xie; Jian Zhang; Yuhao Zhao; Dingliang Xing; Yunga Wu; Johannes Lux; Liang Chang; Kangle Lu; Xin Sun; Donghui Wu; Stefan Scheu (Geoderma)
Understanding seasonal variations in community composition and species distribution along elevation gradients is a core task in biogeography and ecology but remains poorly studied, particularly in soil animal communities. In this study, we assessed seasonal β diversity of Collembola assemblages on Changbai Mountain, China. We sampled 18,942 individuals comprising 96 Collembola species across 10 altitudes (800 –2150 m) and measured five morphological traits (body length, number of ocelli, furca development, pigmentation and scales) of the species across three seasons. We then assessed both incidence-based and abundance-weighted taxonomic as well as functional β-diversity, and partitioned them into species turnover and nestedness, while also considering the contributions of particular species and elevation. Finally, we used multiple regression-based distance matrices to investigate the relative contribution of local habitat-related and climatic factors to β-diversity and their components. Overall taxonomic β-diversity, but not functional β-diversity, increased significantly with elevational distance. Generally, turnover components dominated taxonomic β-diversity across elevations, while both nestedness and turnover equally contributed to functional β-diversity. By contrast, both taxonomic and functional β-diversity varied inconsistently among seasons. The turnover components dominated taxonomic β-diversity across seasons, whereas the nestedness component contributed more to functional β-diversity. Furthermore, the local contribution to overall incidence-based taxonomic β-diversity followed a pronounced U-shaped pattern, indicates that lower and higher elevations significantly contribute to the biodiversity of Collembola communities. Notably, the local contribution to abundance-weighted taxonomic β-diversity decreased significantly with elevation in September but not in May and July. The species contributing to β-diversity varied not only between taxonomic and functional β-diversity but also between seasons. Temperature strongly influenced both taxonomic and functional β-diversity patterns, underscoring its role in shaping Collembola diversity across elevation. Soil pH correlated with functional β-diversity and its turnover component in September but not in May and July. Our findings highlight the importance of incorporating seasonal variations in biodiversity assessments and underscore the contribution of lower and higher elevations to biodiversity conservation in mountainous regions.